How dynamic hedging affects stock price movements: Evidence from German option and certificate markets - Georg Fischer (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2019)
We examine the impact of dynamic hedging demand of German option and discount certificate markets on the autocorrelation of German stock price changes. We theoretically model the demand of liquidity providers in the discount certificate market, a structured financial product with a concave payoff profile, asking whether dynamic hedging by certificate issuers induces negative return autocorrelation in stock markets. We find empirical evidence that the hedging demand of option issuers has a positive impact on return autocorrelation, while the opposite holds for certificate issuers, whose hedging demand enhances the negative return autocorrelation in the stock market. We thus theoretically and empirically provide evidence that there are persistent spillover effects from option and certificate markets to stock markets due to dynamic hedging activities.
Keywords: D40; G12; G21; 650; Structured products; Derivatives; Dynamic hedging; Stock return autocorrelation; Market microstructure